Enhancement of ZnO dye-sensitized solar cell performance by modifying photoelectrodes using an acid vapor texturing process - S. Sutthana (2018)
© 2016 Elsevier B.V. Power conversion efficiency of ZnO dye-sensitized solar cell was enhanced by modifying photoelectrodes using an acid vapor texturing process. Screened ZnO films were modified with HNO3vapor at various texturing time. The modified ZnO films absorbing with N719 dye were used as photoelectrodes for dye-sensitized solar cells. The optimal condition at texturing time of 4 min exhibited the maximum pore density and fine porous films formation. The increase in pore density resulted in better dye adsorption, which was directly correlated to higher short-circuit current density. The cell fabricated with optimal condition obtained the power conversion efficiency of 2.08%, which was mainly due to the increase of short-circuit current density to 6.30 mA/cm2. These results suggested that the acid vapor texturing process can be simply and controllably used to modify porous photoelectrodes for enhancing power conversion efficiency of dye-sensitized solar cells.